2015
DOI: 10.3329/bjms.v14i3.16322
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pilates training in improving hamstring flexibility of football players

Abstract: Abstract:Objective: The kick force is effective only if the flexibility of the muscle is in accord. The stretching capacity of tendons, ligaments and capsule are very limited due to the function of articular stabilization. Pilates exercises are to be performed to improve muscular flexibility with greater movement breadth, strength and fluency. Lack of flexibility is a limiting factor for performance and being a facilitator for muscular injuries. Materials and Methods: Goniometer, Sit and reach table and Exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Flexibility was measured in six studies. Improvement was shown using goniometry, 30 the Pediatric Escola Paulista de Medicina (pEPM-ROM) Scale, postural photographs, the sit and reach test 38 and the toe touch test. 37 Most studies reported a significant increase in flexibility with a large effect size (Table III).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Flexibility was measured in six studies. Improvement was shown using goniometry, 30 the Pediatric Escola Paulista de Medicina (pEPM-ROM) Scale, postural photographs, the sit and reach test 38 and the toe touch test. 37 Most studies reported a significant increase in flexibility with a large effect size (Table III).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As a result of the literature research, it was found out that clinical, reformer pilates exercises had an effect on flexibility values during the training period (Chinnavan et al, 2015;Baştuğ et al, 2014;Aslanoğlu and Şenel, 2013;Demir and Çilli, 2018;Rogers and Gibson, 2009;Karadenizli and Kamur, 2016;Katayıfçı et al, 2014), BMI (Body mass index) is effective in the values (Baştuğ et al, 2014;Abramaviči et al, 2013;Jago et al, 2006), decreased body fat percentage values (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Jago et al, 2006), which are effective in muscle strength parameters (Aslanoğlu and Şenel, 2013;Abramavičiūtč et al, 2013;Sekendiz et al, 2006;Rogers and Gibson, 2009;Katayıfçi et al, 2014), the physical fitness parameters of the environment, skin fold measurement, waist hip ratio, body composition values are effective on (Rogers and Gibson, 2009;Katayıfçı et al, 2014 ;Liman and Güzel, 2008;Gökç elik, 2017) and the Pilates exercise to be effective in physiological parameters (Liman and Güzel, 2008;Temur et al, 2018), has also been found to be effective on balance performance (Katayıfçı et al, 2014;Demir and Çilli, 2018;Atılgan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Pilates is a uniquie form of therapeutic exercise method emphasizing strength, coordination, proprioception, muscle resistance, balance and control, flexibility and mobility, exercise that helps prevent injury. Therefore, by incorporating Pilates into a rehabilitation program, healing period is significantly improved (Cozen, 2000;Chinnavan, 2015;Segal et al, 2004;Jago et al, 2006). Performance improvement can be provided by planning exercises in the light of training science in sportive branch power, flexibility, balance, coordination and timing in technical skills and developing branch-specific reaction skills.…”
Section: Introductionmentioning
confidence: 99%
“…There were many studies in literature reported that pilates exercises had positive effect on flexibility performance. (8,13,22,26,29,30,31). Primarily aim of Pilates exercises was the increasing the flexibility and strength of the body as known by the practitioners.…”
Section: Discussionmentioning
confidence: 99%